OPPO CUSTOMER SATISFACTION ANALYSIS IN PAREPARE ON PRODUCT QUALITY AND PRICE - Nur Iqva Sari Taharuddin; Pandi Putra (International Journal Of Accounting, Management, And Economics Research, 2023)
The purpose of this study is to discover how product quality and price affect client satisfaction at OPPO in Parepare partially and simultaneously. A sample of 45 people from consumers who bought OPPO at Parepare. The t test results indicate that the element of product quality (X1) imply that product quality (X1) has no significant effect on client satisfaction. In fact, many respondents in this study stated that there are still other brands that have better quality. Meanwhile, price (X2) has a significant impact on consumer satisfaction. Because the marketed price is affordable, some respondents choose this product according to the funds they have. The F test results indicate that the variable quality of goods (X1) and price (X2) have an advantageous effect because the quality and price on the market are good and everyone can buy a smartphone with their own budget.